Anticoagulant Prescribing for Non‐Valvular Atrial Fibrillation in the Veterans Health Administration. Issue 17 (3rd September 2019) - Rose, Adam J.; Goldberg, Robert; McManus, David D.; Kapoor, Alok; Wang, Victoria; Liu, Weisong; Yu, Hong
Abstract : Background: Direct acting oral anticoagulants (DOACs) theoretically could contribute to addressing underuse of anticoagulation in non‐valvular atrial fibrillation (NVAF). Few studies have examined this prospect, however. The potential of DOACs to address underuse of anticoagulation in NVAF could be magnified within a healthcare system that sharply limits patients' exposure to out‐of‐pocket copayments, such as the Veterans Health Administration (VA). Methods and Results: We used a clinical data set of all patients with NVAF treated within VA from 2007 to 2016 (n=987 373). We examined how the proportion of patients receiving any anticoagulation, and which agent was prescribed, changed over time. When first approved for VA use in 2011, DOACs constituted a tiny proportion of all prescriptions for anticoagulants (2%); by 2016, this proportion had increased to 45% of all prescriptions and 67% of new prescriptions. Patient characteristics associated with receiving a DOAC, rather than warfarin, included white race, better kidney function, fewer comorbid conditions overall, and no history of stroke or bleeding. In 2007, before the introduction of DOACs, 56% of VA patients with NVAF were receiving anticoagulation; this dipped to 44% in 2012 just after the introduction of DOACs and had risen back to 51% by 2016. Conclusions: These results do not suggest that the availability of DOACs has led to an increased proportion of patients with NVAF receiving anticoagulation, even in the context of a healthcare system that sharply limits patients' exposure to out‐of‐pocket copayments.